Lymphatic Endothelial Cell Junctions: Molecular Regulation in Physiology and Diseases - Zhang, Feng; Zarkada, Georgia; Yi, Sanjun; Eichmann, Anne (Frontiers in Physiology, 2020)
Lymphatic endothelial cells (LECs) lining lymphatic vessels develop specialized cell-cell junctions that are crucial for the maintenance of vessel integrity and proper lymphatic vascular functions. Successful lymphatic drainage requires a division of labor between lymphatic capillaries that take up lymph via open ‘button-like’ junctions, and collectors that transport lymph to veins, which have tight ‘zipper-like’ junctions that prevent lymph leakage. In recent years, progress has been made in the understanding of these specialized junctions, as a result of the application of state-of-the-art imaging tools and novel transgenic animal models. In this review, we discuss lymphatic development and mechanisms governing junction remodeling between button and zipper-like states in LECs. Understanding lymphatic junction remodeling is important in order to unravel lymphatic drainage regulation in obesity and inflammatory diseases and may pave the way towards future novel therapeutic interventions.